Thyroid dysfunction and serum creatinine variations: A tertiary care study from northern Kerala - Revathy B.R; Shivraj Gowda; Sneha Henry (Acta Biochimica Indonesiana, 2026)
Background: Thyroid hormones regulate renal hemodynamics and glomerular filtration rate (GFR), influencing serum creatinine levels. Understanding this relationship is crucial to avoid misclassification of renal function. Objective: To determine the association between thyroid dysfunction and serum creatinine variations in patients attending a tertiary care center. Methods: This retrospective cross-sectional study included 84 thyroid patients (66 females, 18 males) from a tertiary care center in Calicut, Kerala. Participants were classified as hypothyroid or hyperthyroid based on thyroid function tests (TSH, FT3, FT4). Serum creatinine levels were categorized as reduced or elevated using sex-specific reference ranges. Statistical analysis employed chi-square and Fisher's exact tests. Results: Hypothyroid patients exhibited elevated creatinine in 85-100% of cases, while hyperthyroid patients demonstrated reduced creatinine in 92-100% of cases across subgroups. Highly significant inverse associations were observed across all thyroid markers (p<0.001 for all comparisons). The strongest concordance occurred in women younger than 45 years (100% concordance), with modest attenuation in older women (≥45 years), although associations remained highly significant. Conclusion: Thyroid dysfunction profoundly affects serum creatinine through GFR modulation. Clinicians should systematically evaluate thyroid status before diagnosing chronic kidney disease based on creatinine abnormalities to prevent misclassification.